Policy interaction, learning and the fiscal theory of prices - George W. Evans; Seppo Honkapohja (Bank of Finland, 2002)
We investigate both the rational explosive inflation paths studied by McCallum (2001) and the classification of fiscal and monetary policies proposed by Leeper (1991) for stability under learning of rational expectations equilibria (REE).Our first result is that the fiscalist REE in the model of McCallum (2001) is not locally stable under learning.By contrast, in the setting of Leeper (1991), different possibilities can obtain.We find, in particular, that there are parameter domains for which the fiscal theory solution - in which fiscal variables affect the price level - can be a stable outcome under learning.For other parameter domains, the monetarist solution is the stable equilibrium.
URN:NBN:fi:bof-20140807532
Keywords: E52; E31; D84; 330; inflation; expectations; fiscal and monetary policy; explosive price paths